2020
DOI: 10.1093/petrology/egaa049
|View full text |Cite
|
Sign up to set email alerts
|

Timescales and Mechanisms of Crystal-mush Rejuvenation and Melt Extraction Recorded in Permian Plutonic and Volcanic Rocks of the Sesia Magmatic System (Southern Alps, Italy)

Abstract: Silicic calderas can evacuate 100 to >1000 km3 of rhyolitic products in a matter of days to months, leading to questions on pre-eruptive melt generation and accumulation. Whereas silicic plutonic units may provide information on the igneous evolution of crystal-mush bodies, their connection with volcanic units remains enigmatic. In the Ivrea–Verbano Zone of the southern Alps, the plumbing system of a Permian rhyolitic caldera is exposed to a depth of about 25 km in tilted crustal blocks. The upper-crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 161 publications
1
22
0
Order By: Relevance
“…At the same time, Schaen et al (2017) note that a positive Eu anomaly is not required in silicic cumulates if accumulation has occurred from a magma with low Eu concentration. Overall, we find that the Taimyr silicic intrusions have textural characteristics and compositional trends that are consistent with complementary crystal accumulation (i.e., formation of silicic cumulates) and melt segregation (Bachmann and Huber, 2016;Fiedrich et al, 2017;Laurent et al, 2020;Schaen et al, 2017Schaen et al, , 2018Tavazzani et al, 2020).The isotopic composition of Taimyr syenite-granite intrusions (Table S3; Fig. 5) suggests that they were derived from an open magmatic system with a heterogeneous source (Fig.…”
Section: Petrogenesis and Source Of The Taimyr Granitessupporting
confidence: 55%
See 2 more Smart Citations
“…At the same time, Schaen et al (2017) note that a positive Eu anomaly is not required in silicic cumulates if accumulation has occurred from a magma with low Eu concentration. Overall, we find that the Taimyr silicic intrusions have textural characteristics and compositional trends that are consistent with complementary crystal accumulation (i.e., formation of silicic cumulates) and melt segregation (Bachmann and Huber, 2016;Fiedrich et al, 2017;Laurent et al, 2020;Schaen et al, 2017Schaen et al, , 2018Tavazzani et al, 2020).The isotopic composition of Taimyr syenite-granite intrusions (Table S3; Fig. 5) suggests that they were derived from an open magmatic system with a heterogeneous source (Fig.…”
Section: Petrogenesis and Source Of The Taimyr Granitessupporting
confidence: 55%
“…239 Ma and 228 Ma. Large silicic magma chambers are often considered to be upper crustal bodies that are predominantly kept at high crystallinity (e.g., "mush" model; Bachmann and Huber, 2016;Hildreth, 2004;Tavazzani et al, 2020) and episodically recharged by injections from lower crustal reservoirs (Annen et al, 2015;Bachmann and Huber, 2016). Our work characterizes the Taimyr granites as silicic cumulates and elaborates on the connection between silicic magma chambers (crystal mush zones) and large igneous provinces and thereby elucidates the magmatic processes that facilitate the evolution of the continental crust.…”
Section: Thermal Effect Of Siberian Traps Lip Magmatic Pulses On Taimyrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we can conclude that large magma chambers are at least geologically rare since none have been imaged beyond doubt and we have no reason to believe that the present day is special in any way. Many authors have argued that large magma chambers must form quickly before an eruption (e.g., Parks et al, 2012;Cashman et al, 2017;Tavazzani et al, 2020). Different mechanisms have been proposed for how low crystallinity magma may be extracted from mush zones.…”
Section: Melt Fractions In the Crustmentioning
confidence: 99%
“…As amphibole is observed in all Tunis Creek Gabbros, we can test this specific process by comparing the trace element compositions of calculated melts in equilibrium with amphibole to tonalite bulk compositions. Felsic plutonic rocks like the BVIS tonalites can be cumulates formed by removal of erupted melt (Deering and Bachmann, 2010;Gelman et al, 2014;Tavazzani et al, 2020), and it is often difficult to determine the extent to which plutonic rocks with intermediate to felsic compositions represent "true" liquid compositions. However, it has been shown that felsic plutonic rocks (SiO2 > 55-60 wt.…”
Section: Genetic Link Between Mafic Cumulates and Derivative Felsic M...mentioning
confidence: 99%